Dynamic Capabilities To Absorb Knowledge In Promoting Innovative Performance And Organizational Resilience: The Moderating Role Of Organizational Culture - Zara Rafique, Dr. Umer Ayub, Dr. Asif Sanaullah, Dr. Mehtab Alam, Dr. Salima Shahin (Migration Letters, 2024)
Purpose: This study used the Knowledge Based View (KBV) theory to examine the effect of Knowledge Absorptive Capacity (KAC) and Knowledge-based Dynamic Capability (KBDC) on Organizational Resilience (OR) and Organizational Innovative Performance (OIP). The moderating role of Organizational Culture is checked. Moreover, the mediating effect of Organizational Resilience between KAC, KBDC and Innovative Performance is also checked. Design/Methodology/Approach: The population selected and targeted for the research is based upon service and manufacturing industries of Pakistan and analyzed using the structural equation modelling (SEM) technique using SMART PLS. Findings/Results: The findings suggest that an organization can create resilience through the capability of adopting new technology, clear objective, preservation, having diverse solutions and taking rapid action on these solutions. This all can only be achieved if the organization can absorb advanced knowledge of their domain. Research Limitations/Implications: Practically this study indicates that resource and knowledge based dynamic capabilities are grounded in the true expertise of individuals, teams and organizations who can work when proper structures are built, and physical and social resources are distributed evenly. Generalization can be achieved if data from other regional countries is gathered which share common region and similar environment with almost same international competitors. Originality/Value: This study suggests that knowledge absorptive capacity impacts directly on resilience of the organization and makes it more flexible towards innovation. Results show that Organizational Culture strengthens the association between Knowledge Absorptive Capacity and Organizational Resilience. Conclusion: Researchers conclude that to reap the benefits of new trends of competing organizations, organizational executives should highlight the whole process of acquisition & dissemination of knowledge among all levels of workers and must ensure that knowledge and value is being extracted in its true essence.